Perlindungan Hukum Terhadap Waria dari Perlakuan Diskriminatif - Kadek Vegas Ananta Sicaya; I Nyoman Putu Budiartha; Ida Ayu Putu Widiati (Fakultas Hukum Universitas Warmadewa, 2022)
Human rights laws and policies have been made for a long time but the implementation of policies for shemales seems different from ordinary citizens even though they are still Indonesian citizens and have the same rights as citizens. shemale also deserves to be protected by legal protection from acts of violence, harassment, public anarchy, and discrimination and to be treated like other Indonesian citizens by giving them their human rights. The formulation of the problem in this study is: 1) What is the legal protection for transgender women from discriminatory treatment? 2) What are the government's efforts in providing non-discriminatory legal protection for shemale? The research method used is normative law research with a statutory approach. The results of the study show that shemale in Indonesia are still often subject to discrimination such as ridicule, social discrimination, legal discrimination, insults, physical violence to sexual harassment. Getting legal protection is the right of all citizens. Preventive and repressive legal protection provided by law enforcement officials for all citizens is no exception. In order to provide a sense of security, both mentally and physically from interference and various threats from any party.